Grief and functional impairment following COVID-19 loss in a treatment-seeking sample: the mediating role of meaning - Breen, Lauren; Lee, S.A.; Mancini, Vincent O.; Willis, M.; Neimeyer, R.A. (2022)
The COVID-19 pandemic has brought unprecedented levels of grief and psychological distress in community samples. We examined unique pandemic grief risk factors, dysfunctional grief, Post-traumatic Stress Disorder (PTSD) symptoms, general psychiatric distress, disrupted meaning, and functional impairment in a treatment-seeking sample of people bereaved from COVID-19 in the United Kingdom. A sample of 183 participants (91.80% female; M = 47.40 years) completed an online survey as part of an intake assessment for a grief support and referral service. Most reported clinically elevated PTSD symptoms (83.1%), psychiatric distress (64.0%), and functional impairment (56.8%). A smaller, but still concerning percentage (39.3%) reported clinically significant symptoms of dysfunctional grief. Disrupted meaning substantially mediated the relationship between risk factors and all four outcomes. Counsellors should address the breadth of psychological distress in those bereaved by COVID-19 and hone their skills in promoting meaning making in the wake of the trauma and loss generated by the pandemic.